Aspergillus endocarditis presenting as acute right lower limb pain - Ghosh, P; Saha, K (Journal of Pathology of Nepal, 2013)
Corrigendum: On 31/10/2013 the name of the author K. Shah was corrected to read K. Saha. Aspergillus endocarditis is an 2nd most common cause of endocarditis having poor prognosis. We report a rare case of fungal endocarditis following cardiac valve replacement presenting as acute pain in the right lower limb. Embolism and endocarditis were primarily detected by CT angiography and echocardiography respectively. Diagnosis was established by histopathology and culture of the emboli and was confirmed later by isolation of the Aspergillus species from the resected valve tissue. DOI: http://dx.doi.org/10.3126/jpn.v3i6.9002 Journal of Pathology of Nepal (2013) Vol. 3, 502-504